KAJIAN DOSIS PUPUK GUANO DAN UREA TERHADAP PERTUMBUHAN DAN HASIL KACANG TUNGGAK (Vigna unguiculata L.): Kata kunci: Kacang tunggak, kajian, dosis, pupuk, guano, urea. - Sadewo Wahyu Wibowo; Sartono Joko Santosa; Siswadi Siswadi (Innofarm:Jurnal Inovasi Pertanian, 2022)
This research is entitled Study of Guano and Urea Fertilizer Dosage on Growth and Yield of Cowpea (Vigna unguiculata L.). The research was carried out at the Tohudan Food Crops and Horticulture Seed Garden, Karanganyar from December 2021 to February 2022. Using a 2 factor Completely Randomized Design (CRD) and 3 repetition. Guano fertilizer (G) as factor 1 consisted of 4 levels, namely: G0 (Control), G1 = guano at 4.7 grams, G2 = guano at 9.4 grams, G3 = guano at 14.1 grams. Urea fertilizer (N) as factor 2 consisted of 4 levels, namely: N0 = (Control), N1 = urea dose of 2.7 grams, N2 = urea dose of 5.4 grams, N3 = urea dose of 8.1 grams. The data were analyzed using analysis of variance with a further BNJ test with a level of = 5%. The results showed that guano fertilizer (G) had an effect on leaf number, leaf area, dry weight of stover, pod weight, seed weight and seed dry weight with the best dose of 9.4 grams/plant. Urea (N) fertilizer affected plant height, number of leaves, number of pods, pod weight and seed weight with the best dose of 5.4 grams/plant.